Weaning of Macrobrachium rosenbergii (de Man) larvae from Artemia to Moina micrura (Kurz) - Alam, M.J.; Ang, K.J.; Cheah, S.H. (1993)
M. rosenbergii larvae were gradually weaned from Artemia to Moina at their different stages. The feeding regime in which larvae were weaned on to Moina at stage X (AM10M) resulted in the highest (P<0.05) yield of 19.21 ± 1.54 PL/l with a corresponding survival of 64.02 ± 5.14%. After day 11, the survival of larvae fed Artemia alone (A) decreased and at day 31, the value (50.15 ± 5.81% with a corresponding production rate of 15.04±1.74 PL/l) was significantly lower (P<0.05) than those of larvae fed the diets AM8M and AM10M. Larvae fed the weaning diets developed faster at later stages than those fed Artemia alone. © 1993.